Perbedaan Pengaruh Myofascial Release Dan Neuro Development Treatment Terhadap Penurunan Spastisitas Pada Regio Hip, Knee Dan Ankle Anak Cerebral Palsy Spastik Diplegi Di UPT Pusat Layanan Disabilitas Kota Blitar - Febriantama, Mohammad Dhany; Hargiani, Fransisca Xaveria; Kusuma, Wahyu Teja; Halimah, Nurul (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Â To determine the difference between myofascial release and neuro development treatment in reducing spasticity in children with diplegic spastic cerebral palsy.Methods: The number of samples in this study were 20 respondents, which were divided into 2 groups, namely myofascial release and neuro development treatment. The measurement of spasticity in this study uses the Ashworth scale measuring instrument.Results: The results of the wilcoxon test proved that myofascial release had no effect on decreasing spasticity with a p value of 0.083 (p>0.05) in the hip region, p 0.083 (p>0.05) in the knee region and p value 1,000 (p>0.05) in the ankle region, while neuro development treatment had an effect on decreasing spasticity with p value 0.008 (p<0.05) in the hip region, p value 0.005 (p<0.05) in the knee region and p value 0.007 (p<0.05) in the ankle region ankles. The results of the mann-whitney test prove that there is a significant difference in the effect of myofascial release and neuro development treatment on reducing spasticity with a p value of 0.000 (p <0.05).Conclusion: There is a significant difference between myofascial release and neuro development treatment on reducing spasticity in children with spastic cerebral palsy diplegia.